Marketing Information Systems in the Context of Building WOM Marketing Through Service Quality, Institutional Image and Customer Satisfaction in Higher Education - Yani, Tri Endang; Santoso, Aprih; Wibisono, Totok; Kuswardani, DC (International Journal of Artificial Intelligence Research, 2023)
This study aims to construct word of mouth (WOM) marketing through service quality, institutional image, and customer satisfaction as variables influencing higher education institutions. The utility of the research is to help universities create word of mouth to support the sustainability and competitiveness of higher education. The population of this study are still active students at Semarang University. The number of samples is 100 and the selection of the sample ofis a conscious selection based on the criterion of respondents who are studying at least in the 4th semester. The analysis technique used is multiple linear regression and trajectory analysis.The results of the study indicate that the quality of the service and the image of the facility have a partially positive effect on customer satisfaction. The journey analysis, on the other hand, shows that customer satisfaction can neither reflect the relationship between service quality and PTO nor the relationship between image and PTO